A natureza dos logaritmos e aplicações - Moura, Francisco Edson Sousa de (Universidade Federal Rural do Semi-Árido, 2018)
The study of logarithms is undoubtedly a challenge for students in understanding and solving problems and for teachers in presenting the topic in question. This paper aims to help teachers approach a bit of the logarithms a bit differently. At first, we will see how the study of this theme is reported by the curricular parameters and how it is usually inserted in the Enem. After a rapid revision of exponentials is introduced the definition of logarithms based on the book of Elon, 1996. Next, is shown in detail a study on the number e using interest and binomial of Newton, the function ln(x) and several applications of logarithms. Finally, a suggestion is presented to address the exponential function in the room showing its superiority in relation to the other functions
Keywords: Logaritmos; Funções; Aplicações dos logaritmos; Logarithms; Functions; Applications of logarithms; CIENCIAS EXATAS E DA TERRA::MATEMATICA